Involvement of miR164- and miR167-mediated target gene expressions in responses to water deficit in cassava - P. Phookaew; S. Netrphan; P. Sojikul; J. Narangajavana (Biologia Plantarum, 2014)
Cassava (Manihot esculenta Crantz) is an important crop and it is significantly affected by water stress. The computational analysis of cis-regulatory elements in promoter regions of 21 drought-responsive miRNA gene families and 35 miRNA-target genes in cassava indicated some elements relevant to drought stress responses. To investigate the role of miRNAs and target genes in responses to a water deficit in cassava in more detail, in vitro plantlets were subjected to an imitated water deficit by 40 % polyethylene glycol. Using RT-qPCR, the differential expression of the cassava miR164/MesNAC and miR167/MesARF6/8 were observed to be associated with changes in the leaf shape, stomatal closure, and relative water content. The modified 5'-RNA ligase-mediated rapid amplification of cDNA-end (5'RLM-RACE) experiment confirmed MesNAC and MesARF8 as the in vivo-target genes of miR164 and miR167, respectively, in cassava leaf. The possible functions of miR164 and miR167-target genes in response to water deficit are discussed.